Pendekatan Sosio-Ekonomi Potensi Daerah sebagai Pusat Ekstrak Kulit Manggis di Indonesia - Muchtaridi Muchtaridi; Wiwit Nurhidayah; Dini Rochdiani; Luthfi U Setyawati; Risda R Islamiyati; Arif Budiman; Warid Ali Qosim (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
One of the largest mangosteen producing areas in Tasikmalaya Regency, which is in 8 villages in Puspahiang Sub-district. Mangosteen farmers Puspahiang district relies on export quality because the price is 3 times more expensive. However, due to farmers' pursuit of mangosteen the quality of exports of farmers will be much to remove the mangosteen fruit harvest that does not enter the quality of exports such as too small fruits or infected yellow sap disease. In addition, if the mangosteen reached in end season, mangosteen farmers in Puspahiang will switch to other livelihoods. Mangosteen pericarps has been used by generations as a medicine. Socio-economic study to community in the form of the introduction of ECO-friendly technology (TTG) Mangosteen extraction has been aimed to determine the response of mangosteen farmers in Puspahiang in the development of the Mangosteen Extract Center for the needs of the Herbal and Nutrition Medicine industries. The survey method was carried out, socialization, pre-test and post-test. Data were analyzed by descriptive statistics. The socio-economic survey showed that the Puspahiang community is almost 100% in agreement with the construction of the mangosteen leather extrator center. However, 60% of the public is concerned about the processing of waste extracts. Subsequently, it needs to be done waste treatment studies on the socio-economic community.